Clinical and immunological characteristics of diabetes mellitus in patients with autoimmune polyglandular syndrome type 1 in Russia - Leila S. Sozaeva; Lubov I. Zilberman; Galina N. Svetlova; Ekaterina A. Andrianova; Maria A. Kareva; Olga N. Ivanova; Svetlana M. Stepanova; Larisa V. Savelyeva; Alexandr Y. Mayorov; Ekaterina A. Troshina; Elizaveta M. Orlova; Eystein S. Husebye; et al. (Сахарный диабет)
Background. Autoimmune polyglandular syndrome type 1 (APS type 1) is a rare inherited autoimmune disease caused by mutations in AIRE gene (autoimmune regulator) and characterized by list of components. Diabetes mellitus (DM) can be one of components of this disease. Aims. To show frequency of DM in patients with APS type 1 in Russia, to describe clinical and immunological aspects of DM in patients with APS type 1 Materials and methods. 113 patients have been enrolled in the study, 16 of them had DM (15/16) or impaired glucose tolerance (1/16). Antibodies against glutamate decarboxylase, tyrosine phosphatase, zinc transporter-8, insulin and β-cells of pancreas were investigated in 30 patients with APS type 1 without DM and in 11 patients with APS type 1 and DM. ELISA test was used for detection autoantibodies. Results. Frequency of DM in patients with APS type 1 in Russia is 14.1% (16/113). Some patients had slow-progressive DM – 19%(3/16). Antibodies against insulin and β-cells were not specific and also were not sensitive markers for DM in APS type 1. Antibodies against tyrosine phosphatase and zinc transporter-8 test showed high specificity (100% и 97%), but low sensitivity (42% и 33,3%). Antibodies against glutamate decarboxylase were less specific (70%) and had very low sensitivity (58,3%). Conclusions. Frequency of DM in patients with APS type 1 in Russia is high to compare to other countries. 20% of Russian patients had slow-progressive course of DM. Antibodies against tyrosine phosphatase and zinc transporter-8 were the most specific for DM in patients with APS type 1, but sensitivity of these antibodies was low.